?SEED-BoRNE MYCOFLORA OF VEGETABLE SEED LOTS IN NORTHERN AREAS OF PAKISTAN - Khan, M Qasim; Ahmad, S Irfan (Biological Sciences - PJSIR, 1998)
Seed-borne mycoflora of sixty six vegetable seed lots from Northern Areas of Pakistan were examined using the standard blotter technique. Thirteen genera and 21 species offungi were obtained from contaminated seed lots. Alternaria alternata was found in 71.21 % of the seed lots (range 0.5-89.5%), Fusarium moniliforme was recorded in 34.84% of the seed lots (range 0.5-57%) and Penicilium sp were observed in 28.78% of the lots (range 0.5-11. %). Besides these Aspergillus flavus, Alternaria radicina, A tenuissima, Botrytis cinerea, Cephalosporium sp, Chaetomium sp, Cladosporium sp, Curvularia sp, Dichomera sp, Drechslera hawaiiensis, Fusarium culmorum, F equiseti, F nivale, F oxysporum, F semitectum, F solani, Nigrospora sp and Verticil- lium sp, were also encountered from the seed samples.